PENGARUH FREE CASH FLOW, STRUKTUR ASET, RISIKO BISNIS DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG - Prathiwi, Dhyana Intan; Yadnya, I Putu (E-Jurnal Manajemen; Vol 6 No 1 (2017), 2017)
The purpose of this research is to identify the influence of free cash flow, asset structure, business risk and profitability on debt policy. This research was conducted on property and real estate company listed on the Indonesia Stock Exchange in 2009 - 2013. The number of samples taken 23 companies with a purposive sampling techniques and through non-participant observation. Multiple linear regression is used to be data analysis. Summary of research conducted found that the independent variables namely free cash flow, business risk and profitability have significantly influence to debt policy . While asset structure did not have a significant effect on the debt policy. Free cash flow and profitability have significant positive effect on debt policy, the business risk have significant negative effect on debt policy and asset structure have no significant positive effect on debt policy.
Keywords: Free Cash Flow, Asset Structure, Business Risk, Profitability, Debt Policy